PERAN ORANG TUA DALAM MEMBINA AKHLAK ANAK PADA MASA PANDEMI DI RT 64 GANG MAWAR IV PURWAKARTA (Lembaga Pengembangan Kinerja Dosen, 2022)
This research aims to describe the role of parents in developing children's morals during the pademic period at RT 64 Gang Mawa IV Purwakarta. The method used in this research is a descriptive qualitative method. The theory used for the parental role variable is BkkbN eight family functions and al-Ghazali's concept of morals. The results of research on children's moral development during the pandemic by parents are getting used to and teaching children to perform the five daily prayers, getting children used to saying greetings when they want to enter or leave the house, getting used to and teaching children to recite the Koran, and providing supervision in children's social interactions. . Supporting factors for moral development are the participation of religious figures by giving warnings to children who behave badly, the participation of religious figures providing counseling to parents on how to carry out moral formation during the pandemic, families who also supervise children's interactions. The inhibiting factors experienced by parents in developing children's morals are parents' indecisiveness in giving warnings to children, children's inappropriate behavior.